Readiness of Bystander Cardiopulmonary Resuscitation (BCPR) during the COVID-19 Pandemic A Review - Muhammad Fattah Fazel; Mohamad Haiqal Nizar Mohamad; Mohd Azmani Sahar; Norsham Juliana; Izuddin Fahmy Abu; Srijit Das (MDPi, 2024)
Indexed by WOS/SCOPUS/ERA